LEGAL CONSEQUENCES OF SALE AND PURCHASE OBJECTS OF TESTAMENTARY GRANT - Debby Flora Siahaan; Gunawan Djajaputra (Journal of Social Research, 2023)
This writing was motivated by the Surabaya District Court Decision Number 1270/Pdt.G/2021/PN.Sby whose case was regarding the Deed of Sale and Purchase which the object of sale and purchase had been made as an object of a testamentary grant and had been included in the Testament Grant Deed Number 119. The implementation of the sale and purchase is carried out using a Power of Attorney to Sell where the Seller is an elderly woman who is 78 years old and suffers from memory impairment that also known as dementia, so the Seller does not remember that she had made a transaction buying and selling of land that has been given as a testamentary grant. The seller signs the Power of Attorney to Sell without the consent of hes heirs and the sale and purchase was carried out without the knowledge of the seller's family. This writing was written using normative research methods by collecting legal materials regarding testamentary grants and linking Decision Number 1270/Pdt.G/2021/PN.Sby with applicable laws and regulations, and with literature studies in the form of articles that relating to testamentary grants. The conclusion that can be drawn from this research is that the panel of judges has been unwise in carrying out legal considerations in Decision Number 1270/Pdt.G/2021/PN.Sby and the Notary who made the Power of Attorney to Sell must apply the precautionary principle so there will be no dispute over the object of sale and purchase in the future